Beyond the Classroom Wall: A Qualitative Study on the Use of Padlet in Supporting Indonesian High School Students' Writing Skills - Aisyah Febika Irnanda; Siti Mafulah; Uun Muhaji (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2026)
This study explores Indonesian secondary school students' perceptions of using Padlet to support English as a Foreign Language (EFL) writing and examines how the platform facilitates different stages of the writing process. Addressing the limited qualitative evidence on Padlet use among secondary school learners, the study employed a qualitative descriptive design. Data were collected through non-participant classroom observations involving 30 eleventh-grade students and semi-structured interviews with four purposively selected participants at a public senior high school in Malang, Indonesia. The data were analyzed using Braun and Clarke's (2006) thematic analysis, while trustworthiness was established following Lincoln and Guba's (1985) criteria. The findings indicate that Padlet transforms writing from a stressful individual activity into an engaging collaborative process by facilitating idea generation through visual features, reducing handwriting-related anxiety through easy editing, and promoting peer-mediated revision through its commenting feature. Although technical barriers were minimal, prolonged screen use emerged as a potential ergonomic concern. Interpreted through the Technology Acceptance Model (TAM), the findings suggest that students' perceptions of Padlet's usefulness and ease of use contribute to positive engagement in collaborative writing activities. The study contributes to the literature by providing qualitative evidence from Indonesian secondary school EFL learners and offers pedagogical implications for integrating collaborative digital platforms to enhance writing instruction beyond the classroom.